Дослідження В. О. Городцова на Харківщині - Скирда, В. В.; Скирда, І. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary V. Skyrda, I. Skyrda. Researches of Kharkiv Region of V. A. Gorodtsov During the preparation for the 12-th Archeological Congress V. A. Gorodtsov has made a massive archaeological excavations in Izyum District of Kharkiv Province. As a result of these studies scientists have examined several dozens of mounds dating back to the Eneolithic age till the burials of the late nomads. Moreover, the researchers have opened the first drum burial of Saltovska culture near Zlyvky Village and have examined two sites of ancient settlement dating back to the 17-th century. On the grounds of the researches of burial mounds from the Eneolithic to the Bronze Age V. A. Gorodtsov has pointed out such archeological cultures as yamna, catacomb and srubna. Key words: burial, mound, Archaeological Congress, excavations, research.